The embryonic stress response to in vitro culture: insight from genomic analysis. Issue 6 (December 2016) - Cagnone, Gael; Sirard, Marc-André
Abstract : Recent genomic studies have shed light on the impact of in vitro culture (IVC) on embryonic homeostasis and the differential gene expression profiles associated with lower developmental competence. Consistently, the embryonic stress responses to IVC conditions correlate with transcriptomic changes in pathways related to energetic metabolism, extracellular matrix remodelling and inflammatory signalling. These changes appear to result from a developmental adaptation that enhances a Warburg-like effect known to occur naturally during blastulation. First discovered in cancer cells, the Warburg effect (increased glycolysis under aerobic conditions) is thought to result from mitochondrial dysfunction. In the case of IVC embryos, culture conditions may interfere with mitochondrial maturation and oxidative phosphorylation, forcing cells to rely on glycolysis in order to maintain energetic homeostasis. While beneficial in the short term, such adaptations may lead to epigenetic changes with potential long-term effects on implantation, foetal growth and post-natal health. We conclude that lessening the detrimental effects of IVC on mitochondrial activity would lead to significantly improved embryo quality.